Jacques Derrida and the Practice of the Phenomena. Dialectic and Temporality of the Trascendental Exercise (Nóema, 2016)
In this essay I would like to propose a reinterpretation of certain passages of the earlier Derrida’s works, specifically on Edmund Husserl. I will focus mainly on his dissertation (Mémoire d’études superieures) and his Introduction to the Husserlian appendix The origin of geometry. My purpose is to point out some aspects that I consider relevant for the development of the following Derrida’s philosophy. First of all, I’ll try to take into account the concept of dialectic in his transition from Kant to Husserl. Then, starting from Derrida’s interpretation of The Lectures on Internal Time-Consciousness, I’ll try to explain the meaning of what could be described as an aesthetic refoundation of the transcendental. In these early stages Derrida attempted to lay the foundation of what he’ll then call “quasi-transcendental”. From this perspective, we might note that the deconstructive reading – as such – involves a phenomenological attention towards the original contamination between the conditions of possibility and the empirical field. Therefore, the exercise of deconstruction has something to do with difference as différance from the very beginning.
Keywords: Dialectic; time-consciousness; transcendental aesthetic; quasi-transcendental; contamination; exercise; différance